Effect of the New York State cigarette fire safety standard on ignition propensity, smoke constituents, and the consumer market. Issue 5 (23rd September 2005) - Connolly, G N; Alpert, H R; Rees, V; Carpenter, C; Wayne, G F; Vallone, D; Koh, H
Abstract : Objectives: This study examines empirical evidence from the New York experience testing tobacco industry arguments made in opposition to fire safety standards for cigarettes. Design: Percentages of cigarettes exhibiting full length burns (FLBs), cigarette sales before and following the implementation of the New York standards, a sample of retail cigarette prices, brand availability, and selected smoke constituent yields were compared between cigarettes sold in New York and two other states. Cigarette paper analysis was conducted on cigarettes sold in New York. Results: New York cigarette brands averaged 10.0% FLBs as compared to 99.8% for California and Massachusetts brands. Reduced ignition propensity (RIP) appears to have been achieved by cigarette paper banding. Cigarette sales, prices, and brand availability do not appear to have been affected by the New York standards. Yields of the majority of smoke constituents tested did not differ substantially between RIP cigarettes sold in New York as compared to the same brands sold in Massachusetts. Average yields of tar, carbon monoxide, and two compounds were slightly higher, the yields of seven compounds were higher for one brand only, and nicotine was lower, among New York brands tested. Conclusions: RIP cigarette brands have been designed to meet the New York fire safety standards. Their introduction has not affected cigarette sales or prices in New York. There is no evidence that the small increases in smoke constituent yields affect the already highly toxic nature of cigarette smoke. Data on smoking caused fires, deaths, and injuries dating from after the change in law are not yet available. Such data will be able to address the question of whether the demonstrated reduced ignition standards are associated with reduced fires and injuries. Based on the New York experience, prior industry objections to producing RIP cigarettes are unfounded. Other states and nations should adopt similar standards.